Transitioning to the New Normal in Education: A Case Study of Chinese School Leaders in the Philippines - Gina Pecson; Angeline Pogoy (European Scientific Journal, ESJ, 2021)
This paper focuses on exploring the different changing roles and leadership practices of the two Chinese private school leaders in basic education in the new normal with its challenges and opportunities. This case study approach was done through semi-structured interviews and supplemented with documents including e-mails, written reports, meeting notes, and other related documents used for triangulation to strengthen the credibility of outcomes. It also enables different interpretations and meanings to be included in the data analysis. The findings revealed that the two Chinese private school leaders have adapted the four leadership practices successfully in their respective institutions, as they went through the process of restructuring the teaching and learning in the new normal where challenges and opportunities were enormous. These four leadership practices were Situational Leadership, Instructional Leadership, Benchmarking Leadership, and Distributed Leadership that school leaders had to modify and adapt depending on the situations to accommodate an ever-changing environment during and after the COVID-19 pandemic. The adaptability of different changing roles and leadership practices depending on its situations are the essential qualities of school leaders to rise above the circumstances and thrive in crisis during and after the COVID-19 pandemic.